2022
DOI: 10.1016/j.isci.2021.103659
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of functional memory B cells recognizing SARS-CoV-2 variants despite loss of specific IgG

Abstract: While some COVID-19 patients maintain SARS-CoV-2-specific serum IgGs for more than 6 months post-infection, others eventually lose IgG levels. We assessed the persistence of SARS-CoV-2-specific B cells in 17 patients, five of whom had lost specific IgGs after 5–8 months. Differentiation of blood-derived B cells in vitro revealed persistent SARS-CoV-2-specific IgG B-cells in all patients, whereas IgA-B cells were maintained in 11. Antibodies derived from cultured B cells blocked binding of viral receptor-bindin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 75 publications
0
11
0
Order By: Relevance
“…In agreement with those findings, severe COVID 19 induces an exhaustion phenotype on S1-specific IgG + MBCs compared with healthy and recovered individuals ( 34 ). Although SARS-CoV-2-specific antibodies tend to wane over time, the persistence of MBC could supply its lost ( 35 , 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with those findings, severe COVID 19 induces an exhaustion phenotype on S1-specific IgG + MBCs compared with healthy and recovered individuals ( 34 ). Although SARS-CoV-2-specific antibodies tend to wane over time, the persistence of MBC could supply its lost ( 35 , 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…vivax subjects who had recovered from infection for 1–3 months (RCs) and harbored cross-reactive inhibitory antibodies in circulating blood (RC01, RC02, RC03, RC04 and RC06) were used to detect broad MBC responses to DBL-TH variants. PBMCs (1 x 10 6 ) from these RC patients (n = 5) and HCs (n = 4) were transferred into 24-well plates containing 1 mL of culture medium (RPMI + 10% FCS) and subsequently differentiated into antibody-secreting cells (ASCs) with stimulation of R848 (2.5 μg/mL; Invivogen, San Diego, CA, USA) and IL-2 (1,000 IU/mL; Peprotech, Rocky Hill, NJ, USA) at 37°C, 5% CO 2 for 11 days, as previously described [ 23 ]. In this culture system memory B cells differentiated into ASCs [ 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…RBD-specific MBCs that have undergone SHM in GCs and produce high affinity nAbs have frequencies that remain unchanged or even rise 6 months after infection ( 75 , 76 ). Moreover, a recent study showed an encouraging discovery that functional IgG MBCs persist after 5-8 months in infected patients, while the level of serum SARS-CoV-2 specific IgG is eventually lost ( 77 ). This might suggest that the level of MBCs is more sensitive for detection of previous infection and prediction of long-term protection.…”
Section: B Cells Response In Covid-19 Infectionmentioning
confidence: 99%